Manajemen Kelayakan Usaha pada Industri Kecil Menengah Kabupaten Magetan - Pandoyo, Pandoyo; Hidayat, Ahmad; Harimurti, Cundo; Rulandari, Novianita (Batara Wisnu : Indonesian Journal of Community Services, 2022)
The small and Medium Industry is one of the important foundations of the economy of Magetan Regency, so it needs attention for the development of SMEs. One of them is the construction of the Magetan Promotion House which is intended for SMEs to sell and promote their products. This business feasibility analysis training will be guided by modules and speakers, SMIs are taught training in calculating profits, Payback Period, Gross B/C, and NPV based on all costs incurred and revenues obtained in the last 1 month guided by the implementing team. SMEs gain knowledge and skills in analyzing business feasibility as well as knowing the condition of the business from the results of the analysis, which is useful for improving management in future developments